2017
DOI: 10.1038/micronano.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput physical phenotyping of cell differentiation

Abstract: In this report, we present multiparameter deformability cytometry (m-DC), in which we explore a large set of parameters describing the physical phenotypes of pluripotent cells and their derivatives. m-DC utilizes microfluidic inertial focusing and hydrodynamic stretching of single cells in conjunction with high-speed video recording to realize high-throughput characterization of over 20 different cell motion and morphology-derived parameters. Parameters extracted from videos include size, deformability, deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 51 publications
1
68
0
1
Order By: Relevance
“…Previous studies have shown that different microfluidic flow regimes can alter the mechanical response of cells. Gossett et al (14,17,18) developed the technique deformability cytometry (DC) (19,20) in which cells are hydrodynamically stretched at the stagnation point (SP) of an extensional flow device at rates up to 2000 cells/s. A compressional force (F C ) due to fluid inertia and a shear force (F S ) due to fluid viscosity act on the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that different microfluidic flow regimes can alter the mechanical response of cells. Gossett et al (14,17,18) developed the technique deformability cytometry (DC) (19,20) in which cells are hydrodynamically stretched at the stagnation point (SP) of an extensional flow device at rates up to 2000 cells/s. A compressional force (F C ) due to fluid inertia and a shear force (F S ) due to fluid viscosity act on the cells.…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation of progenitor cells is coupled to major changes in their mechanical properties. This is partially due to differences in intracellular organisation and composition [Yourek et al., ; Darling et al., ; Lin et al., ]. In some instances, progenitor mechanical properties can serve as predictive biomarkers for differentiation outcomes [GonzĂĄlez‐Cruz et al., ].…”
Section: Mechanical Evaluation Of Myeloid Cell Differentiationmentioning
confidence: 99%
“…In addition, more improvements in the user interface of microfluidic devices and software are also important requirements for the usage in the clinical situations by clinical doctors, not only by engineers in laboratories. In this paradigm, automation of both the hardware and software is another important topic to be addressed, and has been intensively investigated [91][92][93][94][95]. For the on-chip cell manipulation, we are also developing the automation of the gain-tuning toward clinical usages [96].…”
Section: Medical Applicationsmentioning
confidence: 99%